Bibliotecas públicas como agentes de transformação e redução de desigualdades: uma análise da perspectiva do campo Ciência, Tecnologia e Sociedade - Cerrao, Natalia Gallo (2023)
It is essential that society reflects on its active and questioning role in the use of products and services and also in decisions about science and technology, also to the detriment of informational/digital inclusion and initiatives to combat inequality and unemployment, in particular in today's Information Society. Such observations are concerns and research questions of the Field Science, Technology and Society (STS), and they are being explored in several instances. The main objective of this research is to understand how public libraries operate as agents in the fight against exclusion, inequality, discrimination and misinformation, from the perspective of the Science, Technology and Society (STS) field. In addition, the objective was to identify, in the scientific literature, initiatives and practices that demonstrate the transforming and active role of libraries in society, through proposals for social, technological and informational transformations. In order to achieve the proposed objectives, the methodological procedure of literature review was adopted, performing a search on the CAPES Periodicals Portal through a predefined protocol with search strategies and textual analysis with the creation of a file. Twenty-six articles were identified in accordance with the research objectives, being considered a small number in view of all the content available on the portal. Through the analysis of these articles, it was possible to reflect on the work of libraries and their relationship with the perspectives and reflections of the CTS Field. Among the most expressive activities, storytelling, reading circles, workshops for multiple learning and the availability of computers with Internet access are listed as the ones that were most cited in the retrieved articles, evidencing the expressive performance capacity of the libraries to promote transformations in it’s community.